Mer de Kara, Côte de l'U.R.S.S., Golfes de l'Obi et de l'Enisej (Iénisseï) / d'après les cartes russes publieès de 1930 a 1937 - France. Service hydrographique de la marine (1947)
Janvier 1943 edition no. 2; corrigé . 1947 Relief shown by hachures and spot heights. Depths shown by soundings.; Selected light beacons shown in purple.; Includes 2 inset maps, 16 views and correction information Color; 1:860,000